Comprehensive characterization of mesenchymal stromal cells from patients with Fanconi anaemia. (26th May 2015) - Mantelli, Melissa; Avanzini, Maria Antonia; Rosti, Vittorio; Ingo, Daniela M.; Conforti, Antonella; Novara, Francesca; Arrigo, Giulia; Boni, Marina; Zappatore, Rita; Lenta, Elisa; Moretta, Antonia; Acquafredda, Gloria; et al.
Summary Fanconi anaemia (FA) is an inherited disorder characterized by pancytopenia, congenital malformations and a predisposition to develop malignancies. Alterations in the haematopoietic microenvironment of FA patients have been reported, but little is known regarding the components of their bone marrow (BM) stroma. We characterized mesenchymal stromal cells (MSCs) isolated from BM of 18 FA patients both before and after allogeneic haematopoietic stem cell transplantation (HSCT). Morphology, fibroblast colony‐forming unit (CFU‐F) ability, proliferative capacity, immunophenotype, differentiation potential, ability to support long‐term haematopoiesis and immunomodulatory properties of FA‐MSCs were analysed and compared with those of MSCs expanded from 15 age‐matched healthy donors (HD‐MSCs). FA‐MSCs were genetically characterized through conventional karyotyping, diepoxybutane‐test and array‐comparative genomic hybridization. FA‐MSCs generated before and after HSCT were compared. Morphology, immunophenotype, differentiation potential, ability in vitro to inhibit mitogen‐induced T‐cell proliferation and to support long‐term haematopoiesis did not differ between FA‐MSCs and HD‐MSCs. CFU‐F ability and proliferative capacity of FA‐MSCs isolated after HSCT were significantly lower than those of HD‐MSCs. FA‐MSCs reached senescence significantly earlier than HD‐MSCs and showed spontaneous chromosome fragility. Our findings indicate that FA‐MSCs are defective in their ability to survive in vitro and display spontaneous chromosome breakages; whether these defects are involved in pathophysiology of BM failure syndromes deserves further investigation.